Expression pattern of BMPR-2 and Fas and the regulatory role of BMP-2 and IGF-1 on granulosa cells function in buffalo - VINODKUMAR, D; GULZAR, RAHILA; SELVARAJU, S; NAZAR, S; PARTHIPAN, S; JAMUNA, K V; PRASAD, R V; RAVINDRA, J P (The Indian Journal of Animal Sciences, 2017)
The expression pattern of BMPR-2 and Fas was investigated in different developmental stages (1-3 mm, 3-5 mm, 5-8 mm and >8 mm) of follicles and the effect of bone morphogenetic protein-2 (BMP-2), insulin-like growth factor-1 (IGF-1) and Fas-ligand (Fas-L) was studied in vitro on granulosa cell function. BMPR-2 was mainly localized in the granulosa cells, oocytes and theca cells of healthy follicles from primordial to late antral stages and the expression pattern did not differ among different sizes of follicles. The Fas was predominantly expressed in granulosa cells of atretic follicles. In the granulosa cell culture, BMP-2 (30 ng/ml) and IGF-1 (100 ng/ml) significantly increased estradiol-17β production when compared to control in all sizes i.e. small (3-5 mm), medium (5-8 mm) and large (>8 mm) follicles. This first study in buffalo revealed that BMP-2 rescues small size follicles, whereas IGF-1 rescues all size follicles from Fas mediated apoptosis in buffalo.